Perancangan Aplikasi Dashboard untuk Monitoring Pelayanan Kesehatan pada Puskesmas - Herlina Harahap; Rismayanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Current technological developments have driven acceleration in various fields, especially in the field of information technology. This has led to many advances in software and is also balanced with advances and sophistication in technology and hardware. Directly or indirectly, information technology has become an important part of various areas of life. Because of the many conveniences offered, information technology can hardly be separated from various aspects of human life. Activities that are usually carried out manually or traditionally will be faster and more precise if carried out with the help of technology. Using information technology can increase efficiency in terms of energy, time and costs. The development of information technology also has an impact on the world of work. With the dashboard application for monitoring public health in the city of Medan, it will simplify patient service and administration at each health center. Specifically registration, type of disease, number of patients, gender and referral hospital.